2023
DOI: 10.1051/parasite/2023027
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Cercopithifilaria, Cruorifilaria and Dipetalonema-like filarial nematodes in ticks of French Guiana

Abstract: Filarial nematodes of the Dipetalonema lineage are widespread parasites and include some species that are transmitted by ticks. In this study, we conducted a large molecular survey of ticks in French Guiana, South America, to understand the overall diversity of tick-borne filarioids in this remote region largely covered by dense tropical forests. Out of 682 ticks belonging to 22 species and 6 genera, 21 ticks (3.1%) of the species Amblyomma cajennense, A. oblongoguttatum, A. romitii, Ixodes luciae and Rhipicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Ticks are vectors of major viruses, bacteria, and protozoan parasites of medical and veterinary significance [24,33,34]. However, surveys of tick-borne pathogens often neglect filarial nematodes from the family Onchocercidae, commonly referred to as filariae or filarioids, while these parasites are regularly detected in most tick genera [1,4,6,10,11,17,29,36,39,43,45,46,50,51]. Microscopic observations and molecular typing consistently categorize most tick-associated filarioids into the genera Acanthocheilonema, Monanema, Yatesia, and Cercopithifilaria [1,4,6,10,11,17,29,35,36,39,43,45,46,50,51], although most were initially classified in the genus Dipetalonema [7,9,23].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ticks are vectors of major viruses, bacteria, and protozoan parasites of medical and veterinary significance [24,33,34]. However, surveys of tick-borne pathogens often neglect filarial nematodes from the family Onchocercidae, commonly referred to as filariae or filarioids, while these parasites are regularly detected in most tick genera [1,4,6,10,11,17,29,36,39,43,45,46,50,51]. Microscopic observations and molecular typing consistently categorize most tick-associated filarioids into the genera Acanthocheilonema, Monanema, Yatesia, and Cercopithifilaria [1,4,6,10,11,17,29,35,36,39,43,45,46,50,51], although most were initially classified in the genus Dipetalonema [7,9,23].…”
Section: Introductionmentioning
confidence: 99%
“…However, surveys of tick-borne pathogens often neglect filarial nematodes from the family Onchocercidae, commonly referred to as filariae or filarioids, while these parasites are regularly detected in most tick genera [1,4,6,10,11,17,29,36,39,43,45,46,50,51]. Microscopic observations and molecular typing consistently categorize most tick-associated filarioids into the genera Acanthocheilonema, Monanema, Yatesia, and Cercopithifilaria [1,4,6,10,11,17,29,35,36,39,43,45,46,50,51], although most were initially classified in the genus Dipetalonema [7,9,23]. Phylogenetic analyses based on molecular and morphological data further showed that the genera Acanthocheilonema, Monanema, Yatesia, and Cercopithifilaria (all associated with ticks), as well as Cruorifilaria (not yet associated with a vector, but detected in ticks [17]), Litomosoides (associated with parasitic mites) and Dipetalonema (associated with biting midges), cluster in a monophyletic clade of filarioids, termed the Dipetalonema lineage or the ONC4 clade, within the family Onchocercidae [7,9,23,36].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations